Identification and characterization of acetic acid bacteria species isolated from various sources in Sri Lanka - Kaumal, M. N.; Perumpuli, P. A. B. N.; Buddhika, M. A. A. (Faculty of Science, University of Peradeniya, Sri Lanka, 2021)
Forty-three acetic acid bacteria (AAB) strains were isolated from different types of fruits, flowers and fermented products collected from different regions of Sri Lanka. They were identified using morphological, physiological and biochemical methods. Based on their acetate oxidation pattern, 37 strains of isolated AAB were identified as either Acetobacter or Gluconacetobacter while the rest of the strains were recognized as Gluconobacter. Along with the results of species level identification, isolated strains were identified as A. pomorum, A. aceti, A. pasteurianus, Gluconacetobacter spp. and Gluconobacter frateurii. In order to examine the growth characters of the isolates, they were grown on potato agar plates at 30 ℃, 37 ℃, and 40 ℃, and all the isolated strains revealed good growth at both 30 ℃ and 37 ℃ while A. aceti MS33, A. pomorum SC31, G. frateurii MN12 and MN18 showed good growth even at 40 ℃. Further, it was found that most of the isolated Acetobactertype strains can tolerate up to 10% ethanol even at 37 ℃, and in contrast, the acetate tolerance of all the isolated strains was found to be very poor. Then, acetic acid production ability of AB5, PP21 and SC31 was examined statistically either with 4% of 6% (v/v) ethanol at 30 ℃, 36 ℃ and 37 ℃, and all strains showed over 3.5% (v/v) acetate production either with 4% or 6% initial ethanol up to 36 ℃. Further, A. pasteurianus PP21 gave an acetic acid production of 2.2% with 4% initial ethanol even at 37 ℃. Thus, the obtained results revealed that all three tested strains are prospective applicants in the production of vinegar at higher temperatures

Abstract: Forty-three acetic acid bacteria (AAB) strains were isolated from different types of fruits, flowers and fermented products collected from different regions of Sri Lanka. They were identified using morphological, physiological and biochemical methods. Based on their acetate oxidation pattern, 37 strains of isolated AAB were identified as either Acetobacter or Gluconacetobacter while the rest of the strains were recognized as Gluconobacter. Along with the results of species level identification, isolated strains were identified as A. pomorum, A. aceti, A. pasteurianus, Gluconacetobacter spp. and Gluconobacter frateurii. In order to examine the growth characters of the isolates, they were grown on potato agar plates at 30 ℃, 37 ℃, and 40 ℃, and all the isolated strains revealed good growth at both 30 ℃ and 37 ℃ while A. aceti MS33, A. pomorum SC31, G. frateurii MN12 and MN18 showed good growth even at 40 ℃. Further, it was found that most of the isolated Acetobactertype strains can tolerate up to 10% ethanol even at 37 ℃, and in contrast, the acetate tolerance of all the isolated strains was found to be very poor. Then, acetic acid production ability of AB5, PP21 and SC31 was examined statistically either with 4% of 6% (v/v) ethanol at 30 ℃, 36 ℃ and 37 ℃, and all strains showed over 3.5% (v/v) acetate production either with 4% or 6% initial ethanol up to 36 ℃. Further, A. pasteurianus PP21 gave an acetic acid production of 2.2% with 4% initial ethanol even at 37 ℃. Thus, the obtained results revealed that all three tested strains are prospective applicants in the production of vinegar at higher temperatures.